Healing fractured bones – traditional medicinal plants used by Bodo tribe in Bodoland Territorial Area Districts (BTAD) of Assam, India - Basumatary, Jenima; Thungon, Rinchin Norbu; Lendo, Pakgam Ngulom; Hui, Pallabi Kalita; Das, Abhaya Prasad; Tag, Hui (Ethnobotany Research and Applications, 2025)
Background: People of Bodo tribal community are historically reported to be the early settlers of Assam living in the Bodoland Territorial Area Districts (BTAD) region in the Northwestern part of Assam (India) and they have been using plants from their surroundings since the time immemorial for their survival. The present study focused on the medicinal plants used for the treatment of fractured bone by the Bodo people. Methods: Ethnomedicinal data related to utilization of plants for healing fractured bones were collected through semi-structured interviews of the recognised potential informants. The ethnomedicinal metadata collected was quantitatively assessed to determine Relative Frequency of Citation (RFC), Fidelity Level (FL), and Family Importance Value (FIV). Results: This study revealed the fractured bone healing knowledge system of the selected informants of Bodo community of BTAD which include 80 male and 80 female informants (n=160) and most of them were possessing long term experienced in treating fractured bone. The present study recorded the use of 46 plant species belonging to 36 families of which Amaryllidaceae, Solanaceae, Lamiaceae, and Zingiberaceae contributed 3 species each, then these are followed by Fabaceae, Malvaceae, Myrtaceae, Piperaceae, and Vitaceae (2 spp. each) and the remaining families are represented by 1 species each. These plants are dominated by annual herbs (12 spp., 26.67%), Geophytes (9 spp., 20%), trees (9 spp., 20%), shrubs (5 spp., 11.11%), climber (3 spp., 6.52% each), small trees, geophytic-climber, epiphyte, perennial herb and aquatic herb (1 sp., 2.17%) each. The leaf was reported as highest plant part harvested (43.48%), which was followed by bark, fruits, and whole plant (8.70% each), and for 6.52% plants it was stem and rhizome. Highest RFC value (0.13125) was observed for Cissus quadrangularis, followed by Equisetum ramosissimum var. huegelii (0.09375), and Litsea glutinosa (0.06875). Highest FL has been recorded for Crinum asiaticum, Gomphostemma sp., Aloe vera, Gynura nepalensis, Entada rheedei, Hypericum japonicum, Clerodendrum glandulosum, Hibiscus × rosa-sinensis, Moringa oleifera, Syzygium aromaticum, Persicaria hydropiper, Paederia foetida, Datura metel, Bergera koenigii, Nicotiana tabacum, Thelypteris parasitica, and Curcuma aromatica are with 100% each. The family Vitaceae has the highest FIV of 14.38%, followed by Equisetaceae (9.35%), and Zingiberaceae (8.125%). Conclusion: From the study, it has been realized that the native populations of Bodo tribe living in BTAD, Assam is in favor of continuing uses of medicinal plants to treat fractured bones with which they suffer commonly. However, only the elderly people of the Bodo population are culturing and guarding such priceless plant resources and Traditional Knowledge while the younger generation is interested to take modern allopathic way of treatment. It is now important to record the surviving Traditional Knowledge for future scientific evaluation to support the humanity with modern medicines derived from Traditional Knowledge. Keywords: Ethnomedicinal plants, Bodo tribe, Bone fracture, Healing tradition, BTAD, Assam